Small RNA GadY in Escherichia coli enhances conjugation system of IncP-1 by targeting SdiA - Zhang, Shebin; Long, Jiao; Li, Qiwei; Li, Mo; Yu, Ruiqi; Lu, Yang; Ma, Xingyan; Cai, Yimei; Shen, Cong; Zeng, Jianming; Huang, Bin; Chen, Cha; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Plasmid-mediated conjugation is a common mechanism for most bacteria to transfer antibiotic resistance genes (ARGs). The conjugative transfer of ARGs is emerging as a major threat to human beings. Although several transfer-related factors are known to regulate this process, small RNAs (sRNAs)-based regulatory roles remain to be clarified. Here, the Hfq-binding sRNA GadY in donor strain Escherichia coli (E. coli) SM10λπ was identified as a new regulator for bacterial conjugation. Two conjugation models established in our previous studies were used, which SM10λπ carrying a chromosomally integrated IncP-1α plasmid RP4 and a mobilizable plasmid pUCP24T served as donor cells, and P. aeruginosa PAO1 or E. coli EC600 as the recipients. GadY was found to promote SM10λπ-PAO1 conjugation by base-pairing with its target mRNA SdiA, an orphan LuxR-type receptor that responds to exogenous N-acylated homoserine lactones (AHLs). However, SM10λπ-EC600 conjugation was not affected due to EC600 lacking AHLs synthase. It indicates that the effects of GadY on conjugation depended on AHLs-SdiA signalling. Further study found GadY bound SdiA to negatively regulate the global RP4 repressors KorA and KorB. When under ciprofloxacin or levofloxacin treatment, GadY expression in donor strain was enhanced, and it positively regulated quinolone-induced SM10λπ-PAO1 conjugation. Thus, our study provides a novel role for sRNA GadY in regulating plasmid-mediated conjugation, which helps us better understand bacterial conjugation to counter antibiotic resistance.